Gestión de conocimiento y portales de conocimiento empresarial Paradigma empresarial y tecnológico - Bolaños Castro, Sandro Javier; Pérez Castillo, José Nelson (Ingeniería, 2001)
This paper makes a reflexive review of the main ideas proposed by knowledge management which are exposed by some of its principal exponents, likewise it examines knowledge portals and the contributions that these offer in the knowledge management frame, highlight them as the first pragmatic application and valuable tool at the moment of implementing this model into an organization.